A pathway to negative acculturation: marital maladjustment mediates the relationship between the length of residency and depressive symptoms in immigrant women in Taiwan - Mei-Huei Lien; Sheng-Shiung Huang; Hao-Jan Yang (BMC, 2021)
Abstract Background Immigrant women in Taiwan experience a variety of acculturative and marital problems that result in a mental-health problems. We examined the mediational effect of marital adjustment on the relationship between acculturation and depressive symptoms in immigrant women in Taiwan. Methods All participants (N = 127) were interviewed to collect data regarding their basic sociodemographics, depressive symptoms, acculturation (using language proficiency and years in Taiwan as indicators), and marital adjustment. We used a Sobel test to examine how marital adjustment mediates the relationship between acculturation and depressive symptoms. Results Our results indicated that an increased length of residency exacerbated depressive symptoms (β = 0.62, p = 0.03) and that this relationship contributed, in part, to the mediational effect of marital adjustment. That is, marital adjustment deteriorated with the length of residency (β =  − 0.26, p = 0.0013), resulting in the development of depressive symptoms (β =  − 0.95, p = 0.0013). Conclusion Although the duration of residency may be useful as a proxy for acculturation in the assessment of some health outcomes, our findings imply that it is better to conceptualize it as a cumulative stress when considering the mental health of immigrant women. Marital maladjustment acts as a mediator in this relationship. As such, it is important to provide immigrant families with programs and resources to assist them in adapting to their marriages and to improve the mental health of immigrant women.